Black hole apocalypse [videorecording (DVD)] - DeNooyer, Rushmore (PBS Distribution, 2018)
Join astrophysicist and novelist Janna Levin on a mind-blowing voyage to the frontiers of black hole science, which is shining new light on the most powerful and mysterious objects in the universe.